Two moss species from Mt Durmitor new to the bryophyte flora of Montenegro - Vulevic, Anja; Dragicevic, Snezana; Petrovic, Danka (Acta Botanica Croatica, 2017)
The present paper reports the first records of two moss species, Orthotrichum obtusifolium Brid. and Dicranoweisia cirrata (Hedw.) Lindb., in the flora of Montenegro. The mosses were found in the Tepacki kraj area on Mt Durmitor. Some morphological features, the ecological characteristics and the distribution of the species are given, along with photographs of diagnostic details and their threat status in the countries of SE Europe.